PENGARUH PERPUTARAN PERSEDIAAN, PERPUTARAN KAS DAN PERSEDIAAN PIUTANG RENTABILITAS EKONOMIS (STUDI PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR FOOD AND BEVERAGES YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2012-2016) - Runtunuwu, Clara C.; Alexander, Stanly W.; Wokas, Heince R. N. (Universitas Sam Ratulangi, 2017)
The purpose of this study to determine the effect of inventory turnover, cash turnover, and receivable turnover to economic profitability as measured by Return On Assets (ROA). Sample selection was done by purposive sampling method and from 16 manufacturing companies food and beverages sub sectors obtained 11 samples of the company. The data used is secondary data. This study analyzes the relationship between the number of inventory turnover, cash turnover, and receivable turnover to economic profitability as measured by Return On Assets (ROA). The statistical method used is multiple linear regression by doing the classical assumption test first. The results of this study show that partially variable inventory turnover significant effect on economic profitability measured by Return On Assets (ROA), cash turnover significant effect on economic profitability as measured by Return On Assets (ROA), and turnover receivables have no significant effect on profitability economic value as measured by Return On Assets (ROA) in manufacturing companies food and beverages sub sector listed in Indonesia Stock Exchange (IDX).Keywords: Inventory turnover, Cash turnover, Receiveable turnover, Economic profitability,Â Return On Assets.